Invisible connections : an archaeometallurgical analysis of the Bronze Age metalwork from the Egyptian Museum of the University of Leipzig - Odler, Martin (Archaeopress Egyptology, 2020)
The Egyptian Museum of the University of Leipzig has the largest university collection of ancient Egyptian artefacts in Germany. This volume presents an analysis of 86 of these artefacts using a range of archaeometallurgical methods in order to provide a diachronic sample of Bronze Age Egyptian copper alloy metalwork from Dynasty 1 to Dynasty 19